2019
DOI: 10.1186/s12872-019-1188-y
|View full text |Cite
|
Sign up to set email alerts
|

Short- and medium-term follow-up of transcatheter closure of perimembranous ventricular septal defects

Abstract: Background Transcatheter closure of perimembranous ventricular septal defects is one of the greatest challenges in interventional cardiology. Short- and midium-term follow-up data for large samples are limited. This report presents our experience with transcatheter closure of perimembranous ventricular septal defects using an occluder. Methods Two hundred fifty-three patients included in the database of the Second Affiliated Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 9 publications
(9 reference statements)
1
20
0
Order By: Relevance
“…The incidence of postprocedural LAFB ranges from 3.6 to 5.5% as reported by other centers (13)(14)(15). Our results indicate that postprocedural LAFB has an incidence of 2.2% (30/1,371) among all patients and 11.8% (30/255) among all postprocedural arrhythmias, and it is not that low, especially among postprocedural BBB (23.3%, 30/129).…”
Section: Discussionsupporting
confidence: 69%
“…The incidence of postprocedural LAFB ranges from 3.6 to 5.5% as reported by other centers (13)(14)(15). Our results indicate that postprocedural LAFB has an incidence of 2.2% (30/1,371) among all patients and 11.8% (30/255) among all postprocedural arrhythmias, and it is not that low, especially among postprocedural BBB (23.3%, 30/129).…”
Section: Discussionsupporting
confidence: 69%
“…cAVB has been considered to be the most serious complication, 2 , 11 with rate of incidence gradually decreasing to 1% in recent years. 12 , 13 , 14 CLBBB draws more attention because definite proof from clinical and experimental studies has identified that CLBBB might cause abnormal LV contraction and deteriorate LV function, which could induce progressive LV remodeling and heart failure. 15 Special attention was paid to the possibility of recurrence and late onset of cAVB and CLBBB.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been no cross-sectional comparison between the two treatments, so research on the different effects of these two treatments on the postoperative HRQoL of adult patients is still needed. [18][19][20][21] In this study, we found that there was no significant difference in SF-36 scores between groups A and B except for the two dimensions of vitality and mental health. The reason might be that the patients subjectively felt that the transcatheter procedure had less impact on the body than the transthoracic procedure and thus had more positive feedback in the psychological domain.…”
Section: Discussionmentioning
confidence: 53%